2012
DOI: 10.1073/pnas.1211314109
|View full text |Cite|
|
Sign up to set email alerts
|

Triclosan impairs excitation–contraction coupling and Ca 2+ dynamics in striated muscle

Abstract: Triclosan (TCS), a high-production-volume chemical used as a bactericide in personal care products, is a priority pollutant of growing concern to human and environmental health. TCS is capable of altering the activity of type 1 ryanodine receptor (RyR1), but its potential to influence physiological excitation–contraction coupling (ECC) and muscle function has not been investigated. Here, we report that TCS impairs ECC of both cardiac and skeletal muscle in vitro and in vivo. TCS acutely depresses hemodynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 55 publications
7
122
2
3
Order By: Relevance
“…El TCS, por su estructura similar a tóxicos que alteran las funciones musculares, puede inducir alteraciones en los receptores rianodina tipo 1 y tipo 2, ambos canales intercelulares mediadores de la liberación del ion Ca++ desde el retículo sarcoplásmico, siendo el Ca++ necesario para la acción del músculo esquelético y cardiaco. De manera que el TCS disminuye la capacidad y fuerza de contracción del músculo cardiaco en ratones (35). Pero contrario a lo observado en el modelo in vivo, en un estudio clínico incluyendo 438 pacientes, no se encontró ninguna relación entre el uso de PTCS durante 5 años y enfermedad cardiovascular (36).…”
Section: Evaluación De Efectos Del Triclosán En Humanosunclassified
“…El TCS, por su estructura similar a tóxicos que alteran las funciones musculares, puede inducir alteraciones en los receptores rianodina tipo 1 y tipo 2, ambos canales intercelulares mediadores de la liberación del ion Ca++ desde el retículo sarcoplásmico, siendo el Ca++ necesario para la acción del músculo esquelético y cardiaco. De manera que el TCS disminuye la capacidad y fuerza de contracción del músculo cardiaco en ratones (35). Pero contrario a lo observado en el modelo in vivo, en un estudio clínico incluyendo 438 pacientes, no se encontró ninguna relación entre el uso de PTCS durante 5 años y enfermedad cardiovascular (36).…”
Section: Evaluación De Efectos Del Triclosán En Humanosunclassified
“…In this study a mouse was given a dose that was less than 1% of what is considered to be lethal to animals. The mouse died within a minute of being given the dose of heart failure [4]. This is an important find because; disruption of Ca2+ signaling in humans can cause heart failure in humans as well.…”
Section: Heart Muscle Cells and Human Skeletal Studymentioning
confidence: 99%
“…The researches of this study altered the dosage to a lesser than the previous 1% (>12.5um) and found that the Triclosan still altered the ability for the heart to move blood and weaken the strength of the leg muscles in the mice [4].…”
Section: Heart Muscle Cells and Human Skeletal Studymentioning
confidence: 99%
See 2 more Smart Citations